Sitotoksisitas Fraksi Piper porphyrophyllum terhadap Sel Kanker T47D - Yus Hargono Cahyaning Yudi; Hartanto Nugroho (Biology Department, Faculty of Science and Technology, Univeristas Jambi, Indonesia, 2016)
Genus Piper has been using traditionally as medicines. Piper aborescen, P. crocatum, P. Imperiale, P. longum, and P. methysticum have ability to inhibit breast cancer proliferation. This research goal is to know cytotoxic activity of Piper porphyrophyllum fraction against T47D cancer cell. Extraction it’s leaves use soxhlet with chloroform as solvent then use vacuum liquid chromatography. Cytotoxic activity of Piper porphyrophyllum fraction determined by MTT assay. The result showed that fraction group A has lowest IC50 (36.22 µg/ml).